INTEGRATIVE MEDICINE THROUGH ISLAMIC PERSPECTIVE IN RESPECTING PANDEMIC COVID-19 - Meity Elvina (International Islamic Medicine Forum, 2020)
One of the problems in the world today is the outbreak of the coronavirus pandemic case. The case of this pandemic outbreak also cannot be separated from the problems known to Muslims. Overall, Al-Quran and al-Hadith explain about many stories that we might be able to take the event of ibrah. Islam's perfection has provided many solutions to various kinds of problems that arise by a Muslim, including the coronavirus pandemic, which is of considerable concern to humans worldwide. Muslim needs to have his own perspective in responding to this coronavirus outbreak's pandemic incident. So that we can do our best to overcome the pandemic case of the coronavirus outbreak by